Characterization of regulatory genes Plhffp and Plpif1 involved in conidiation regulation in Purpureocillium lavendulum - Wei, Yu; Qi, Feng-Na; Xu, Yan-Rui; Zhang, Ke-Qin; Xu, Jianping; Cao, Yan-Ru; Liang, Lian-Ming (Frontiers in Microbiology, 2024)
Purpureocillium lavendulum is an important biocontrol agent against plant-parasitic nematodes, primarily infecting them with conidia. However, research on the regulatory genes and pathways involved in its conidiation is still limited. In this study, we employed Agrobacterium tumefaciens-mediated genetic transformation to generate 4,870 random T-DNA insertion mutants of P. lavendulum. Among these mutants, 131 strains exhibited abnormal conidiation, and further in-depth investigations were conducted on two strains (designated as #5-197 and #5-119) that showed significantly reduced conidiation. Through whole-genome re-sequencing and genome walking, we identified the T-DNA insertion sites in these strains and determined the corresponding genes affected by the insertions, namely Plhffp and Plpif1. Both genes were knocked out through homologous recombination, and phenotypic analysis revealed a significant difference in conidiation between the knockout strains and the wild-type strain (ku80). Upon complementation of the ΔPlpif1 strain with the corresponding wildtype allele, conidiation was restored to a level comparable to ku80, providing further evidence of the involvement of this gene in conidiation regulation in P. lavendulum. The knockout of Plhffp or Plpif1 reduced the antioxidant capacity of P. lavendulum, and the absence of Plhffp also resulted in decreased resistance to SDS, suggesting that this gene may be involved in the integrity of the cell wall. RT-qPCR showed that knockout of Plhffp or Plpif1 altered expression levels of several known genes associated with conidiation. Additionally, the analysis of nematode infection assays with Caenorhabditis elegans indicated that the knockout of Plhffp and Plpif1 indirectly reduced the pathogenicity of P. lavendulum towards the nematodes. The results demonstrate that Agrobacterium tumefaciens - mediated T-DNA insertion mutagenesis, gene knockout, and complementation can be highly effective for identifying functionally important genes in P. lavendulum.